Acute kidney injury and the critically ill. Issue 2 (February 2021) - Flood, Laura; Nichol, Alistair
Abstract: Acute renal failure is commonly encountered in the intensive care unit. It is associated with considerable morbidity and mortality. There are many possible aetiologies in the critically ill, including nephrotoxic agents, hypovolaemia and sepsis. While many classification systems for acute renal failure exist, the RIFLE (Risk, Injury, Failure, Loss, End-stage) criteria and the Acute Kidney Injury Network (AKIN) criteria are the most commonly utilized. Many supportive therapies are employed to minimize the degree of renal injury once recognized, such as fluid resuscitation, maintenance of an adequate mean arterial pressure (with the use of vasopressors in persistent hypotension despite fluid and treatment of the underlying aetiology). However, if renal failure becomes established, then renal replacement therapy (RRT) may be needed to maintain homeostasis. While there are no clear guidelines with respect to the ideal mode or timing of RRT, we will discuss pros and cons of the various options.